2021
DOI: 10.3389/fgene.2021.662080
|View full text |Cite
|
Sign up to set email alerts
|

Identification of key Genes and Pathways Associated With Thermal Stress in Peripheral Blood Mononuclear Cells of Holstein Dairy Cattle

Abstract: The objectives of the present study were to identify key genes and biological pathways associated with thermal stress in Chinese Holstein dairy cattle. Hence, we constructed a cell-model, applied various molecular biology experimental techniques and bioinformatics analysis. A total of 55 candidate genes were screened from published literature and the IPA database to examine its regulation under cold (25°C) or heat (42°C) stress in PBMCs. We identified 29 (3 up-regulated and 26 down-regulated) and 41 (15 up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 78 publications
(106 reference statements)
4
12
0
Order By: Relevance
“…Numerous studies have revealed the Hsp90aa1 gene can be significantly upregulated in a tissue-specific and time-dependent manner after heat stress [71]. Moreover, our previous study also confirmed the important role of HSP70AA1 in dairy cattle [72]. Thus, the Hsp90aa1 plays pivotal role in heat stress response.…”
Section: Differentially Expressed Novel Transcript Lengths For Genes ...supporting
confidence: 81%
“…Numerous studies have revealed the Hsp90aa1 gene can be significantly upregulated in a tissue-specific and time-dependent manner after heat stress [71]. Moreover, our previous study also confirmed the important role of HSP70AA1 in dairy cattle [72]. Thus, the Hsp90aa1 plays pivotal role in heat stress response.…”
Section: Differentially Expressed Novel Transcript Lengths For Genes ...supporting
confidence: 81%
“…The estrogen signaling pathway is a temperature-sensitive pathway. It can be induced by not only cold stress but also by heat stress [ 55 , 56 ]. Estrogens are not only crucial in sexual maturation and reproduction but are also highly involved in a wide range of brain functions, and they play crucial roles in skeletal muscle homeostasis and exercise capacity [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…We were particularly interested in identifying the long-term effect of thermal stress on cell proliferation, differentiation, and immunomodulation capacities; as those key MSC features were amongst the most abundant GO term groups. To examine the relevance of our data to physiological heat stress, we compared our DEGs to a list of 55 genes defined as thermal stress responsive in a bovine study done in vivo (Fang et al, 2021): 36 of the 55 genes were found to be differentially expressed following short, long or both HS groups. The genes EIF2A, HSPA1A, HSP90AA1, and HSF1 were considered by the authors key genes that responded to thermal stress of Holstein dairy cattle.…”
Section: Discussionmentioning
confidence: 99%